Relationship of Healthy Building Determinants With Back and Neck Pain: A Systematic Review. Issue 1 (January 2023) - Gherscovici, Ezequiel D.; Mayer, John M.
Objective: Back pain and neck pain are very common, costly, and disabling. Healthy building determinants within the built environment have not been adequately assessed as contributors to these conditions. The objective of this study was to systematically review the literature on the relationship of healthy building determinants with back and neck pain. Data Source: PubMed, CINAHL, EMBASE, Google Scholar, and PEDRo. Study Inclusion and Exclusion Criteria: Studies were included if they met the following criteria: Adults, comparison of healthy building determinants (air quality, ventilation, dust and pests, lighting and views, moisture, noise, safety/security, thermal health, water quality) with back and neck pain, original research, English. Studies were excluded if full text articles were unavailable and if the focus was patient and materials handling or ergonomics. Data Extraction: Data extraction and other review procedures were elaborated according to PRISMA guidelines. Data Synthesis: Data were synthesized with an approach adapted from Oxford Centre for Evidence-Based Medicine and American Physical Therapy Association. Results: 37 articles enrolling 46, 223 participants were eligible. Most articles were cross-sectional (31/37) and fair quality (28/37). None were interventional. Evidence was found to generally support a relationship indicating that as healthy building determinants worsen, the risk of back and neck pain increases. Conclusion: Although the available evidence precludes interpretations about causality, the study's findings are starting points to guide future research, knowledge creation, and health promotion initiatives about the relationships of the built environment with back and neck pain.